(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes the formation and development of the postal-telegraph system in the Fergana Region during the late 19th and early 20th centuries based on historical sources. The study relies on the decisions of the Postal-Telegraph Main Administration of the Russian Empire, statistical reports of the Turkestan General-Governorate, archival documents, еarbooks, materials from the newspaper “Turkestanskiye Vedomosti,” and the travel notes of Henry Lansdell. The research highlights the establishment of postal-telegraph services, their financial support, the construction of postal routes and telegraph lines, and the issues associated with their operation. It also identifies the role of the imperial administration, local population, and foreign observers in shaping the communication system and its importance in the socio-economic life of the Fergana Valley.